Oxford advanced learners dictionary of current english A.S. Hornby ; editor, Colin Mclntosh, Joanna Turnbull - HORNBY, A.S; Melntosh, Colin; Turnbull, Joanna (Oxford University Press, 2005)
xii, 2940 hlm. : ilus. ; 24 cm.